The Silent Workforce Revolution: Are Workers Engaging in Stealth Use of Generative Artificial Intelligence and Reaping Career Gains? - Campello de Souza, Bruno; Serrano de Andrade Neto, Agostinho; Roazzi, Antonio (AI and Tech in Behavioral and Social Sciences, 2025)
Generative Artificial Intelligence (GenAI) is reshaping workplace dynamics, often informally and without explicit employer endorsement. Using data from 576 professionals in Recife's Metropolitan Region, Brazil, we study the implications of GenAI use in organizations through the lenses of Cognitive Mediation Networks Theory (CMNT) and Actor-Network Theory (ANT). Specifically, we investigate the associations of the internalization of AI-mediated reasoning (Sophotechnia) with sociodemographic factors, psychological traits, and career success. Findings indicated that Sophotechnia is primarily a cognitive trait developed through experience with GenAIs. This trait is particularly fostered by an exploration-oriented personality. Organizationally, while 81.0% of the workers had interacted with GenAI, only 22.6% were employed in organizations that had formally adopted AI tools. Of those that had engaged with the technology, the vast majority used it for knowledge acquisition or construction (92.2%), and writing, interpreting or manipulating texts (83.4%). Those with higher levels of Sophotechnia exhibited not only greater confidence in the positive impacts of GenAIs (62.9% of users believed in a personal positive impact versus 15.2% of the non-users), but also superior job performance (81.3% chance of exceeding work requirements among those with high Sophotechnia versus only 27.6% for those in the lower range). Additionally, Sophotechnia showed a positive association to the speed of career growth (Rho=.37), plus greater satisfaction with job rewards (Rho=.29) and workplace relationships (Rho=.15). There was yet a positive correlation with the time spent working from home (Rho=.26), but not to the overall time spent working (Rho=.03). These findings highlight a disconnect between individual and corporate AI strategies. Workers seem to independently use GenAIs at home to improve their performance and obtain benefits, often without their employers’ awareness. This poses a managerial challenge for organizations to strategically integrate GenAI and maximize its benefits while addressing ethical and regulatory challenges.